Pemanfaatan Key Opinion Leader (KOL) Brand Scarlett Whitening dalam Pemasaran Digital Pada Generasi Z - Erwin Permana; Abdiel Reihan; Alvito Daffa Gustyo; Syamsurizal, Syamsurizal (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
In facing the rapidly developing digital era, Scarlett Whitening has succeeded in combining traditional business principles with digital marketing methods. One important approach taken is through collaboration with Key Opinion Leaders (KOL) on various social media platforms, such as Instagram and TikTok. With appropriate KOL support, Scarlett Whitening succeeded in reaching generation Z, its main target market, with a more personal approach and in line with brand needs. This research aims to analyze the use of KOL brand Scarlett whitening in Generation Z. The research was conducted using a descriptive qualitative approach. Research data comes from search results in various digital databases and literature reviews. The research results show that by utilizing Key Opinion Leaders (KOL) in digital marketing strategies, Scarlett Whitening has succeeded in aligning the use of KOLs in its digital marketing strategy, such as through collaboration with KOLs who have significant influence and reach among the younger generation. The selected KOLs are not only popular because of their large number of followers, but also the content they present is of high quality and suits the interests and needs of the target market. Scarlett Whitening's main target market is teenagers aged 15-34 years, namely Generation Z, who have a tendency to be very familiar with digital technology. With a more personal approach and in line with the needs of the target market, Scarlett Whitening has succeeded in reaching generation Z with quality content that suits the interests and needs of the target market. The content produced by KOL for Scarlett Whitening often contains product reviews, usage tutorials, and testimonials from consumers. Through this content, information about the quality, safety and effectiveness of the Scarlett Whitening brand can be conveyed in an authentic and convincing way to potential consumers.